2016
DOI: 10.1002/lt.24349
|View full text |Cite
|
Sign up to set email alerts
|

Effect of scavenger receptor class B type I antagonist ITX5061 in patients with hepatitis C virus infection undergoing liver transplantation

Abstract: Hepatitis C virus (HCV) entry inhibitors have been hypothesized to prevent infection of the liver after transplantation. ITX5061 is a Scavenger Receptor B-I (SR-BI) antagonist that blocks HCV entry and infection in vitro. We assessed the safety and efficacy of ITX5061 to limit HCV infection of the graft. The study included 23 HCV infected patients undergoing liver transplantation. The first 13 “control” patients did not receive drug. The subsequent 10 patients received ITX5061 150 mg immediately pre- and post-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 40 publications
(54 reference statements)
2
32
0
Order By: Relevance
“…We 12 and others 13, 14 have previously reported a rapid decrease in HCV RNA within the first 16 hours following surgery due to clearance of virus in the periphery by the reticular endothelial system of the new liver. To assess the influence of transplant time on viral clearance and allograft infection kinetics we calculated the area over the infection curve for control and treated subjects between 0–16 h and 24–168 h after transplantation ( Figure 3C, D).…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…We 12 and others 13, 14 have previously reported a rapid decrease in HCV RNA within the first 16 hours following surgery due to clearance of virus in the periphery by the reticular endothelial system of the new liver. To assess the influence of transplant time on viral clearance and allograft infection kinetics we calculated the area over the infection curve for control and treated subjects between 0–16 h and 24–168 h after transplantation ( Figure 3C, D).…”
Section: Resultsmentioning
confidence: 78%
“…The data presented were obtained from subjects enrolled in an open-label phase 1b study to assess the effect of ITX5061 in patients undergoing liver transplantation at a single centre (Queen Elizabeth Hospital Birmingham, Birmingham, UK), described previously 12 . All patients gave informed written consent and ethical approval was given by the UK National Research Ethics Service (reference 10/H0301/36) 12 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Monoclonal antibodies that block CD81 or SR-BI protected against subsequent HCV challenge with different genotypes in human liver chimeric mice [200][201][202]. The anti-SR-BI entry inhibitor ITX5061 has been tested in the clinic [203,204], and showed some evidence of reducing HCV RNA titers and viral evolution in patients undergoing liver transplantation [203]. An antibody against Claudin-1 can control HCV in human liver chimeric mice [205].…”
Section: Hcv Co-receptorsmentioning
confidence: 98%
“…The anti-HCV effect of ITX 5061 was found additive to synergistic in combination with several standard-of-care therapeutics, and the resistant mutant was defined on the viral glycoprotein E2 [123]. A latest phase 1b clinical trial [124] revealed that the ITX 5061-treated patients, especially the genotype 1-infected patients, had a significant reduction in HCV RNA through the first week after liver transplantation and viral evolution were restricted; however, the viral RNA levels became comparable in both ITX 5061-treated and untreated patients, suggesting the need to incorporate other antiviral agents using different modes of actions to eliminate HCV infection. Aspirin, alternatively, inhibited HCV entry by downregulating CLDN1 [125].…”
Section: Small Molecules Targeting Host Entry Factors and Cd81-triggementioning
confidence: 99%